2020
DOI: 10.1186/s12885-020-07695-3
|View full text |Cite|
|
Sign up to set email alerts
|

Comprehensive analysis of prognostic gene signatures based on immune infiltration of ovarian cancer

Abstract: Background Ovarian cancer (OV) is one of the most common malignant tumors of gynecology oncology. The lack of effective early diagnosis methods and treatment strategies result in a low five-year survival rate. Also, immunotherapy plays an important auxiliary role in the treatment of advanced OV patient, so it is of great significance to find out effective immune-related tumor markers for the diagnosis and treatment of OV. Methods Based on the conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 93 publications
1
17
0
Order By: Relevance
“…Similar to our study, Millstein et al (19) and Yan et al (20) used bioinformatics analysis to confirm CXCL9 and CXCL11 were associated with better OS in OC patients, respectively. Both CXCL9 and CXCL11 could recruit T and B lymphocytes and natural killer cells to inhibit tumor growth, and the expression of CXCL11 was closely related to antigen-related genes, immune checkpoint-related genes, and PARPi therapy (21).…”
Section: Eight-gene Prognostic Modelsupporting
confidence: 85%
“…Similar to our study, Millstein et al (19) and Yan et al (20) used bioinformatics analysis to confirm CXCL9 and CXCL11 were associated with better OS in OC patients, respectively. Both CXCL9 and CXCL11 could recruit T and B lymphocytes and natural killer cells to inhibit tumor growth, and the expression of CXCL11 was closely related to antigen-related genes, immune checkpoint-related genes, and PARPi therapy (21).…”
Section: Eight-gene Prognostic Modelsupporting
confidence: 85%
“…Regarding the regulatory function of lymphocytes, some evidence showed that T cell subsets (Th1, Treg ( Motz and Coukos, 2011 ) and CD4 + Th2 cells ( DeNardo et al, 2009 )) could also play pro-angiogenesis roles through different mechanisms. Previous studies showed that poor prognosis of cancer patients is greatly correlated with the proportion of M2-like TAMs ( Ni et al, 2019 ; Yan et al, 2020 ; Wang et al, 2021 ; Ye et al, 2021 ). Therefore, whether high risk score is positively correlated with M2-like macrophages needs to be further confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…The included studies 11,35–47,54–61 used models built based on the TCGA cohort and involved all types of breast cancer. The final results showed that our signature and three other prognostic signatures, namely, a 21 immune‐related gene signature, 35 17 immune‐related gene signature 36 and 17 TF‐related gene signature 37 performed better than the other hallmark signatures in the prediction of OS in patients with OV 11,35,38–47,54–61 . Additionally, Yu et al has constructed a five GRG signature (ANGPTL4, PYGB, ISG20, SEH1L and IRS2) for patients with OV 62 .…”
Section: Discussionmentioning
confidence: 99%
“…To further explore the predictive ability of our signature, a comparison was performed among several significant molecular signatures that were employed for predicting OS in patients with OV. The included studies 11 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 used models built based on the TCGA cohort and involved all types of breast cancer. The final results showed that our signature and three other prognostic signatures, namely, a 21 immune‐related gene signature, 35 17 immune‐related gene signature 36 and 17 TF‐related gene signature 37 performed better than the other hallmark signatures in the prediction of OS in patients with OV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation